Design and Performance Evaluation of a Soybean Filtration Machine Utilizing an Electric Motor and Low-Torque Gearbox - Nur Fatta, Muhammad Affa; Dwi Saputro, Danang; Hidayat, Hanif (Rekayasa, 2025)
The traditional soybean filtration process in small- and medium-scale tofu industries remains inefficient due to labour-intensive operations, inconsistent extract quality, and high processing time. Manual pressing methods often result in reduced extract yield, uneven texture, and contamination risks. Therefore, this study aims to design and evaluate a soybean filtration machine powered by an electric motor and a low-torque gearbox, with the goal of improving efficiency, hygiene, and mechanical reliability. The research employed a Research and Development approach using the Four-D model: define, design, develop, and disseminate. A 0.5 hp electric motor was integrated with a 1:20 ratio gearbox to achieve stable rotational motion for the reciprocating filter system. The mechanical analysis indicated a total working force of 613.725 N, a motor torque of 61.37 Nm, and an output torque of 1,105 Nm after accounting for efficiency. The system demonstrated low structural deflection (0.405 mm) and a high safety factor of 3.81, confirming robust mechanical integrity. Experimental testing yielded a filtration efficiency of 93% and an average flow rate of 1.2 L/min, showing a 70–80% reduction in processing time compared to manual filtration. The feasibility assessment resulted in an 88.63% approval rating from operators, classifying the machine as highly feasible. Overall, the designed system effectively improves productivity, ergonomics, and product consistency in soybean-based food processing.